Preface: 4th IWR Special Issue on Scientific Computing - Bock, Hans Georg; Capasso, Vincenzo; Jäger, Willi; Hoang Xuan Phu (Vietnam journal of mathematics, 2021)
Whereas the Life Sciences were fields historically concerned largely with qualitative understanding of phenomena and inferring processes from patterns, the present avalanche of data in particular at the molecular and cellular level and the progress in computer technology have encouraged a more quantitative approach beginning from information on processes at the micro and even nano level.
Gesehen am 30.06.2021